Cantaré e cantaría / cantarei e cantaria - Müller Pograjc, Blažka (Verba hispanica, 2014)
In this article we contrast the Spanish and Portuguese future and conditional, as well as the straight and dislocated uses of these verb forms in these two languages, and observe that the vector concept, developed and proposed for the Spanish language by the Spanish linguists Rojo and Veiga, can be adapted for the description of these linguistic phenomena in both languages The first case of the dislocation (migration for Bull (1968)), as described by the linguists, leading to modal concepts of uncertainty, is unique, both in ES and in PT, to those indicative verb forms in which straight time value obligatorily intersects some vector of posteriority. These forms are cantaré, cantaría / cantarei, cantaria and their corresponding composite forms. Through this dislocation, the vector of posteriority is suppressed and replaced with the vector of simultaneity. Considering the second case of the dislocation leading to modal concept of irreality, this may appear in that certain indicative forms in which straight time value obligatorily acquires some vector of anteriority, in particular, in the indicative forms cantaría / cantari
Keywords: pogojnik; future tense; prihodnjik; modalne vrednosti; vektorski sistem; portugalščina; Spanish; španščina; časovna razmerja